PENINGKATAN KEMAMPUAN BERBICARA DENGAN PENDEKATAN KONTEKSTUAL MELALUI MEDIA AUDIO VISUAL - Gultom, Aemi Lisonda (2014)
Untukberbicaradalamsituasi yang tidakresmi, parasiswatidakbanyakmengalamikesulitan, merekadapatberbicaradenganlancar.Berbedahalnyaapabilasiswadihadapkansuatupembicaraan yang sifatnyaresmi, misalnyadiskusiataupidatoatauberbicaradi depankelas, banyak di antaramereka yang sulitmengungkapkangagasan.Kesulitanberbicarasiswakelas VI dalammengemukakangagasanpadasuasana formal atauresmi di depankelasBerdasarkan hasil wawancara dan pengamatan penulis di SDN Cempaka Baru 01 ditemukan karena seringnyapara guru menggunakanteknikceramahuntukmenjelaskanbahan ajar.Walaupunadasiswa yang mauberbicaratapistrukturnyamasihberbelit-belitdankurangsistematissehinggatidakterjadikomunikasi yang baikantarasipembicaradansipenyimak, bahkanadabeberapasiswa yang samasekalisulitdalammengemukakangagasanuntukberbicara.Penelitianinimembahas: (1) bagaimanaperencanaanpembelajaranyang dapatmeningkatkankemampuanberbicaradenganpendekatankontekstualmelalui media audio visual?, (2) bagaimana proses pembelajaran yang dapatmeningkatkankemampuanberbicaradenganpendekatankontekstualmelalui mediaaudio visual?,(3) bagaimanahasilpembelajaranberbicaradenganpendekatankontekstualmelalui media audio visual?. Metodepenelitian yang digunakanadalahpenelitiantindakankelasdenganmetodekualitatifdandeskriptifdengansubjekpenelitianadalahsiswakelasenamtahun 2013-2014 SDN CempakaBaru 01 Pagi Jakarta Pusatdenganjumlah31 orang siswa.Hasiltindakandalampembelajaranberbicaradenganpendekatankontekstualmelalui media audio visual sangatefektifuntukpenguasaanhubungandengantopikdenganisi, strukturisi, keberaniandankelancaranberbicara, berdasarkanhasiltindakansiklus I sampaidengansiklus III mengalamipeningkatan. Kata kunci :Kemampuanberbicara, PendekatanKontekstual, Media Audio Visual To speak in formal situations,the students did not experience any difficulties, they can speak fluently. Unlike the case when students are exposed to a conversation that an official nature, such as discussions or speeches or speaking in front of the class, many of them are difficult to express ideas. Difficulty speaking sixth grade students in expressing ideas in a formal or formal atmosphere in front of the class Based on interviews and observations of the author in New Cempaka SDN 01 is found as often teachers use the lecture to explain the techniques of teaching materials.While there are students who want to talk but its structure is still convoluted and less systematically so there is good communication between the speaker and the penyimak, even some students at all difficult to put forward ideas to talk . This study discusses : ( 1 ) how learning plan that can improve the ability to speak with a contextual approach through audio-visual media ?, ( 2 ) how the learning process can improve the ability to speak with a contextual approach through audio-visual media ?, ( 3 ) how the learning outcomes talk with contextual approach through audio-visual media?. The research method used was action research with qualitative methods and descriptive research subject is the 2013-2014 sixth grade students of SDN 01 Morning New Cempaka Jakarta Pusat the number of 31 students. Action results in learning to talk with contextual approach through audio-visual media is very effective for control of the relationship with the subject content, the content structure, courage and eloquence, based on the results of the first cycle of action until the third cycle has increased. Key words : ability to speak , Contextual Approach , Media Audio Visual